Exponential Decay of Energy for a Logarithmic Wave Equation (Journal of Partial Differential Equations, 2015)
" In this paper we consider the initial boundary value problem for a class of logarithmic wave equation. By constructing an appropriate Lyapunov function, we obtain the decay estimates of energy for the logarithmic wave equation with linear damping and some suitable initial data. The results extend the early results."